ANALYSIS OF PHARMACY SERVICE QUALITY ON KIDNEY PATIENT SATISFACTION AT ROYAL PRIMA HOSPITAL - Simanjuntak, Mafe Robbi; Zega, Nensi Febriani; Manalu, Putranto (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2025)
High-quality pharmacy services are a crucial component in supporting patient satisfaction, particularly for kidney patients who require continuous medication monitoring and management. This study aims to analyze the relationship between pharmacy service quality including physical facilities, reliability, responsiveness, assurance, and empathy and the satisfaction level of kidney patients at Royal Prima Hospital in Medan City. A quantitative approach with a cross-sectional design was employed, using a structured questionnaire administered to 100 respondents. The results indicate that all dimensions of pharmacy service quality are significantly associated with patient satisfaction (p < 0.05). These findings suggest that comprehensive improvements in pharmacy services contribute to enhanced satisfaction among kidney patients. Therefore, hospitals are encouraged to prioritize and optimize pharmaceutical care as an integral part of quality healthcare delivery.